Manual de poscosecha de frutas. Manejo integrado de patógenos - Murray, Ricardo Ernesto (INTA Ediciones, 2019)
Reedición de: Murray, Ricardo E.; Candán, Ana P. ; Vázquez, Daniel E. (eds.) Manual de poscosecha de frutas. Manejo integrado de patógenos. C.A. Buenos Aires: Ediciones INTA, 2012. ISBN978-987-679-274-5